2015
DOI: 10.1097/opx.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatism and Early Academic Readiness in Preschool Children

Abstract: The presence of astigmatism detected in a screening setting was associated with a pattern of reduced academic readiness in multiple developmental and educational domains among at-risk preschool-aged children. This study may help to establish the role of early vision screenings, comprehensive vision examinations, and the need for refractive correction to improve academic success in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…27 Orlansky et al compared measures of early academic readiness for preschool children (3 to 5 years olds enrolled in a Head Start) with no astigmatism to preschoolers with astigmatism (≥0.50D in either eye) and found that the presence of astigmatism was associated with lower scores on several measures of academic readiness. 28 Our findings are consistent with results from studies of school based samples: ORF was significantly reduced in astigmatic students when they were not wearing their spectacle correction in comparison to students with little or no astigmatism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…27 Orlansky et al compared measures of early academic readiness for preschool children (3 to 5 years olds enrolled in a Head Start) with no astigmatism to preschoolers with astigmatism (≥0.50D in either eye) and found that the presence of astigmatism was associated with lower scores on several measures of academic readiness. 28 Our findings are consistent with results from studies of school based samples: ORF was significantly reduced in astigmatic students when they were not wearing their spectacle correction in comparison to students with little or no astigmatism.…”
Section: Discussionsupporting
confidence: 90%
“…25,26 In contrast, two studies using school-based samples found significant relations between astigmatism and academic performance and readiness in children. 27,28 In a study of Navajo (Diné) Native American school children, who have a high prevalence of astigmatism, Garber reported that uncorrected astigmatic 5 th and 6 th grade students (≥2.00D) had poorer teacher-assigned reading scores than non-astigmatic students, but found no significant effect of astigmatism on reading scores from standardized tests in 2 nd grade students. 27 Orlansky et al compared measures of early academic readiness for preschool children (3 to 5 years olds enrolled in a Head Start) with no astigmatism to preschoolers with astigmatism (≥0.50D in either eye) and found that the presence of astigmatism was associated with lower scores on several measures of academic readiness.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperopic refractive error has been found to be strongly correlated with delayed reading skills and lower academic performance in children . In addition, a recently published study also found a correlation between astigmatism and reading difficulties . Our purpose was to determine eye movement differences between good and poor readers, not to investigate subtle optometric differences.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies examine whether or not variability in visual tasks predict non-visual abilities or performance. Orlansky et al (2015) found that variability in astigmatism measured in preschool-aged children predicted various forms of reduced academic readiness in various developmental and educational domains, and Wilmer and Buchanan (2009) found that nearpoint phorias after near work predict ADHD symptoms in college students.…”
Section: The Value Of Research On Individual Differencesmentioning
confidence: 99%